Exosomes As Potential Biomarkers and Targeted Therapy in Colorectal Cancer: A Mini-Review - Hon, Kha Wai; Abu, Nadiah; Ab Mutalib, Nurul-Syakima; Jamal, Rahman (Frontiers in Pharmacology, 2017)
The number of colorectal cancer (CRC) cases have increased gradually year by year. In fact, CRC is one of the most widely diagnosed cancer in men and women today. This disease is usually diagnosed at a later stage of the development, and by then, the chance of survival has declined significantly. Even though substantial progress has been made in understanding the basic molecular mechanism of CRC, there is still a lack of understanding in using the available information for diagnosing CRC effectively. Liquid biopsies are minimally invasive and have become the epitome of a good screening source for stage-specific diagnosis, measuring drug response and severity of the disease. There are various circulating entities that can be found in biological fluids, and among them, exosomes, have been gaining considerable attention. Exosomes can be found in almost all biological fluids including serum, urine, saliva and breast milk. Furthermore, exosomes carry valuable molecular information such as proteins and nucleic acids that directly reflects the source of the cells. Nevertheless, the inconsistent yield and isolation process and the difficulty in obtaining pure exosomes have become major obstacles that need to be addressed. The potential usage of exosomes as biomarkers have not been fully validated and explored yet. This review attempts to uncover the potential molecules that can be derived from CRC-exosomes as promising biomarkers or molecular targets for effective diagnosing of CRC.